YTHDF2 Regulates Maternal Transcriptome Degradation and Embryo Development in Goat - Deng, Mingtian; Chen, BaoBao; Liu, Zifei; Cai, Yu; Wan, Yongjie; Zhang, Guomin; Fan, Yixuan; Zhang, Yanli; Wang, Feng (Frontiers in Cell and Developmental Biology, 2020)
Maternal mRNA clearance is critical for the early embryo development, which is under the tight control of RNA N6-methyladenosine (m6A). However, little information is known regarding the maternal mRNA clearance and mechanisms behind it in farm animals. In the present study, 3362 differentially expressed genes (DEGs) were found during the maternal-to-zygotic transition (MZT) and determined as maternal mRNAs in goat. Of which, 1961 was decreased at the 4-cell stage embryos, while 1401 was trigged down-regulation at the 8-cell stage embryos, which were termed as maternally encoded mRNA decay genes and zygotic genome activation (ZGA)-dependent maternal mRNAs, respectively. The expression of m6A reader YTHDF2 was increased during goat ZGA, and knockdown of YTHDF2 resulted in decreased blastocyst rate. In the 8-cell stage YTHDF2 knockdown embryos, the M-decay and Z-decay maternal mRNA clearance were impaired. Specifically, the expression of de-adenlyase (CNOT1 and CNOT11) and decapping enzymes (DCP1A and DCP2) was decreased. In conclusion, we ascertained maternal mRNAs and inferred that maternal mRNA clearance is also ZGA-dependent in goat. We reported that YTHDF2 is vital for goat early embryogenesis as it advances maternal mRNA clearance, which might through the recruitment of deadenylases and mRNA decapping enzymes. This work will be of great value for understanding the stochastic reprogramming events during MZT and achieving better development of goat embryos in vitro. Keywords: Embryogenesis, Maternal-to-zygotic transition, N6-methyladenosine, YTHDF2, maternal mRNA decay, zygotic genome activation.